Therapeutic use of colchicine and its derivatives: a patent review. (2nd October 2016) - Mandhare, Anita; Banerjee, Paromita
ABSTRACT: Introduction : Colchicine, the major alkaloid extracted from the meadow saffron ( Colchicum autumnale) is one of the most prominent natural products belonging to the class of organic compounds known as tropones. Colchicine's medicinal properties have been long-known, but it has been attracting renewed attention due to its action as an antimitotic agent. Areas covered : This review presents an update and analysis of the patents claiming therapeutic activity of colchicine and its derivatives published in the last five years (2010–2015). Other patents claiming the application of colchicine in the areas of biotechnology, veterinary, and agriculture are therefore excluded from this review. Expert opinion : Rapid increase in the number of publications and patent filings in recent years for the significant therapeutic potential of colchicine, for several conditions beyond gout, clearly indicates the growing interest of research on this molecule. Although the molecular structure of colchicine fulfils the four Lipinski's requisites for high oral bioavailability, the toxic side effects resulting from its fast metabolism need to be assessed. Further efforts are therefore required to explore the appropriate dosage and possible administration techniques of colchicine for practical use.